Deficit irrigation and fertigation increases the productive performance of lettuce cv. Veneranda (Research, Society and Development, 2020)
The objective of this study was to evaluate the behavior of morphophysiological parameters of venerated lettuce under different layers of water and fertigation. The experiment was carried out at the Arapiraca Campus, UFAL. The design was in randomized blocks (DBC), with four blocks, arranged in a 5 x 5 factorial. The treatments consisted of five water levels (L): 50, 75, 100, 125 and 150% of the Culture Evapotranspiration (ETc), expressed in mm day-1, determined by five drainage lysimeters present in the area, correlated to five levels of fertigation: 50, 75, 100, 125, and 150. The localized drip irrigation system was used. At 30DAT, the data were collected, tabulated, and submitted to analysis of variance and the F test (P